Approximate Solution of linear Fredholm-Volterra Integro- Differential Equations of Two-Dimensional (Journal of the College of Basic Education, 2023)
The research aims to find approximate solutions for linear Fredholm-Volterra Integro- Differential Equations of type two dimensions. Using the two-variables of the Bernstein polynomials to find the approximate solution of mixed linear Fredholm-Volterra Integro- Differential Equations of the type two dimensions. Two examples discussed in detail.